El método de proyectos en geotecnia vial caso: balasto para vía férrea Belencito – Paz del Río1 (2019)
The article is a research product at Santo Tomás University. The project method in Road Geotechnics was applied in railways, since it is a process that is beginning to be used in several universities around the world. In this regard, interviews and observations were made to establish the changes in the competences. Learning environments were used, such as laboratory tests, field work, visits to quarries, sampling and simulation with test sections and the main advances are described. Although the iron material is used for steelmaking, the option of using it in a seat layer and as a granular subbase was established. On the other hand, iron ore was extracted, irrigated on the road and two test sections of 25 meters each were obtained to be analyzed in the field for six months and prices were studied. The laboratory tests were: Los Angeles Machine Wear, Sand Equivalent, Elongation and Flattening Index, Percentage of fractured faces and Atterberg Limits. The main results are framed in the increase and construction of disciplinary and human competences and in the option to use the gravel material as a seat layer and the distance to which it is possible and profitable to put it. The kindliness of the project method to structure skills in engineers is taken as a relevant conclusion.